Essays on semantic content and context-sensitivity - Yli-Vakkuri, TJ (2012)
The thesis comprises three foundational studies on the topics named in its title, together with an introduction. Ch. 1 argues against a popular combination of views in the philosophy of language: Propositionality, which says that the semantic values of natural language sentences (relative to contexts) are the propositions they express (in those contexts) and Compositionality, which says that the semantic value of a complex expression of a natural language (in a context) is determined by the semantic values its immediate constituents have (in that same context) together with their syntactic mode of combination. Ch. 1 argues that the Naïve Picture is inconsistent with the presence of variable-binding in natural languages. Ch. 2 criticizes the strategy of using “operator arguments” to establish relativist conclusions such as: that the truth values of propositions vary with time (Time Relativism) or that they vary with location (Location Relativism). Operator arguments purport to derive the conclusion that propositions vary in truth value along some parameter P from the premise that there are, in some language, sentential operators that operate on or “shift” the P parameter. I identify two forms of operator argument, offer a reconstruction of each, and I argue that both they rely on an implausible, coarse-grained conception of propositions. Ch. 3 is an assessment of the prospects for semantic internalism. It argues, first, that to accommodate Putnam’s famous Twin Earth examples, an internalist must maintain that narrow semantic content determines different extensions relative to agents and times. Second, that the most thoroughly worked out version of semantic internalism – the epistemic two-dimensionalism (E2D) of David Chalmers – can accommodate the original Twin Earth thought experiments but is refuted by similar thought experiments that involve temporally or spatially symmetric agents.